Development of an object-oriented framework for the vibration characteristic computation of multibody systems. (October 2020) - Chen, Gangli; Rui, Xiaoting; Gu, Junjie; Zeng, Xiaoyun; Liu, Xingbao
Highlights: Object-oriented technology is used to develop a vibration characteristic solver. A novel data structure based on binary tree is proposed for multibody systems. A recursive formula for deriving overall transfer matrix is proposed. The automatic deduction of overall transfer matrix by computer is achieved. Engineering application is realized on an ultra-precision fly cutting machine tool. Abstract: Vibration characteristic is one of the most important properties for structures and mechanical systems. Transfer matrix method for linear multibody systems (linear MSTMM) is an efficient approach to computing the vibration characteristics of such systems due to its following features: easy to formulate, high programming, and low-order matrix without system global dynamic equations. In this work, a vibration characteristic solver based on linear MSTMM is developed by adopting object-oriented programming (OOP) technique. Binary tree is employed to describe multibody system topology. Then, a novel approach combining sequence and chain storage structures is proposed to store the element data and topology of multibody system. A recursive formula is proposed to derive the overall transfer matrix of multibody system, and its automatic deduction and computation by computer are achieved. The object-oriented framework of the solver is developed to realize the vibration characteristic computation. Furthermore, the numerical study for a Stewart parallel mechanism as well as the practical engineering example of an ultra-precision fly cutting machine tool are performed to validate the solver.